AN ANALYSIS OF SOCIAL CLASSES AND CONFLICTS IN KEVIN KWAN’S CRAZY RICH ASIAN NOVEL: Social Class, Crazy Rich Asia, Social Conflict. - Risma Kartika Dewi; Ira Nur Fitrianah (Fakultas Sastra Universitas Gresik, 2021)
The writer uses Crazy Rich Asian novel By Kevin Kwan as an object. This analysis discusses how the social class contained in the Crazy Rich Asian novel and its conflict on family life. In this thesis, the writer uses the social class and social conflict theory to analyze the novel. The method used in writing this thesis is a qualitative descriptive method. The findings and analysis that can be found in the novel about social class differences. This class difference is created because of the existence of social class, where they classify their social class, namely the upper class and middle class. Where the upper classes do not want to accept the middle class into their class. The difference in social class is measured by the power or wealth, privileges and prestige that affect the position, lifestyle, habits and behavior between the upper class and middle class so that the gap between the two classes is so striking. The conflict is the gap in social status in a family life or relationship. This gap affects the thinking of upper families who cannot accept any class lower than them to enter their families.